Neuroprotective effect of nose-to-brain delivery of Asiatic acid in solid lipid nanoparticles and its mechanisms against memory dysfunction induced by Amyloid Beta1-42 in mice - Ridho Islamie; Su Lwin Lwin Myint; Tissana Rojanaratha; Garnpimol Ritthidej; Oraphan Wanakhachornkrai; Onsurang Wattanathamsan; Ratchanee Rodsiri (BMC, 2023)
Abstract Background Amyloid-β1-42 (Aβ1-42) plays an essential role in the development of the early stage of Alzheimer's disease (AD). Asiatic acid (AA), an active compound in Centella asiatica L, exhibit neuroprotective properties in previous studies. Due to its low bioavailability, the nose-to-brain delivery technique was used to enhance AA penetration in the brain. In this study, AA was also loaded in solid lipid nanoparticles (SLNs) as a strategy to increase its absorption in the nasal cavity. Methods Memory impairment was induced via direct intracerebroventricular injection of Aβ1-42 oligomer into mouse brain. The neuroprotective effect and potential underlying mechanisms were investigated using several memory behavioral examinations and molecular techniques. Results The intranasal administration of AA in SLNs attenuated learning and memory impairment induced by Aβ1-42 in Morris water maze and novel object recognition tests. AA significantly inhibited tau hyperphosphorylation of pTau-S396 and pTau-T231 and prevented astrocyte reactivity and microglial activation in the hippocampus of Aβ1-42-treated mice. It is also decreased the high levels of IL-1β, TNF-α, and malondialdehyde (MDA) in mouse brain. Conclusions These results suggested that nose-to-brain delivery of AA in SLNs could be a promising strategy to treat the early stage of AD.